Cor triatriatum sinister e hipertensão arterial pulmonar secundária em cão - Champion, T.; Gava, F.n. [UNESP]; Garrido, E. [UNESP]; Galvão, A.l.b. [UNESP]; Camacho, A.a. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2014)
This paper describes the occurrence of cor triatriatum sinister, a rare cardiac malformation in dogs, associated with pulmonary edema and pulmonary hypertension in a 5-year-old Poodle female with history of acute dyspnea and cyanosis. The animal presented acute respiratory failure, heart failure with low cardiac output, progressing to acute tubular necrosis and death. The diagnosis was made posmortem due to the clinical instability of the dog. This malformation was diagnosed by the subdivision of the left atrium into two compartments separated by an abnormal fibromuscular membrane, absence of structural abnormalities of the mitral valve and thickening of pulmonary artery tunica media associated with renal tubular degeneration. The occurrence of cor triatriatum in dogs is most common in the right atrium, defined as cor triatriatum dexter. Additionally, pulmonary arterial hypertension associated with this malformation is described only in humans with this heart defect.
Cor triatriatum sinister and secondary pulmonary arterial hypertension in a dog
Keywords: cardiopatia congênita; átrio esquerdo; doença vascular pulmonar; congenital heart defect; left atrium; pulmonary vascular disease